Optimization of maritime emergency base placement for inland waterway accident response: a case study of the Yangtze River - Quandang Ma; Jiaquan Pan; Yang Zhou; Shaorui Zhou; Mingyang Zhang (Brodogradnja)
As the construction of maritime emergency rescue systems worldwide increases, there are more maritime emergency bases along the Yangtze River, yet the mismatch between the layout of these bases and the demand for maritime emergency rescue has emerged. This paper analyzes the impact of marine transportation accident characteristics on emergency demand, uses the CRITIC assignment method to quantify the weights of accident characteristics, and classifies accident levels via the WRSR method. It introduces the equivalent accident number method’s research idea and employs the DBSCAN algorithm to cluster and analyze accident blackspots on the Yangtze River mainline. Based on identified blackspots and multiple siting model characteristics, an emergency base siting model considering accident emergency demand is proposed and solved with LINGO. Taking the accident cases in the Nanjing section of the Yangtze River from 2019 to 2021 as an example, a siting scheme meeting the emergency demand of the Yangtze River trunk line is obtained. Model validation results show that at least three maritime emergency facilities need to be built in the Nanjing section to ensure comprehensive coverage of main navigable waters. As the number of emergency facilities grows, their comprehensive emergency response time decreases and multiple coverage of high-risk waters can be achieved. Decision-makers can formulate emergency facility layout plans based on the proposed siting method.